By-passing of P-glycoprotein using immunoliposomes - Huwyler, Jörg; Fricker, Gert (Journal of drug targeting, 2002)
The over-expression of MDR1 P-glycoprotein has been associated with the development of multidrug-resistance in cancer cells. Methods used to overcome multidrug-resistance often involve the co-administration of inhibitors of P-glycoprotein. Here, we test the hypothesis that an immunoliposome-based drug delivery system may be used as an alternative approach to overcome multidrug-resistance since immunoliposomes penetrate target cells by receptor-mediated endocytosis which allows to by-pass membrane-associated P-glycoprotein. Targeting of immunoliposomes was achieved by the use of an anti-transferrin receptor monoclonal antibody (OX26 mAb). Incorporation of radiolabelled digoxin within OX26-immunoliposomes enhanced cellular uptake of digoxin by a factor of 25 in immortalised RBE4 rat brain capillary endothelial cells. Uptake of liposomal digoxin was insensitive to ritonavir, a P-glycoprotein inhibitor, and was reduced in presence of increasing free concentrations of OX26 mAb or nocodazole, a reversible inhibitor of endocytosis. In contrast, uptake of free digoxin was enhanced by a factor of 1.8 in presence of ritonavir and was insensitive to OX26 mAb or nocodazole. Cellular uptake and intracellular accumulation of liposomal digoxin (55% internalisation within 30 min) was demonstrated by acid wash of the cells and was confirmed by confocal microscopy studies. Endosomal release to the cytosol of propidium iodide loaded immunoliposomes was shown. These in vitro studies suggest that immunoliposome-based drug delivery systems can be used to by-pass P-glycoprotein and thus deliver drugs to the cytosol of a target cell.
Gesehen am 25.04.2017